The structural relationships of problem solving skills and spiritual intelligence with internet addiction tendency according mediating role of rumination - Fatemeh Hazrat bagi; Parviz Asgari; Behnam Makvandi; Amin Koraei (مجله علوم روانشناختی, 2022)
Background: The results of research indicate that the Internet addiction, as an impulse control disorder and maladaptive pattern of Internet use, leads to significant disruption in cognitive, academic and occupational problems in a person's life. In addition, the rumination or thoughts that the individual has repeatedly in their mind about negative felings and events might lead to catatrophizing. Although many studies have focused on problem - solving strategies and spiritual intelligence as preventative skills to improve coping with traumatic events, there is a research gap in the context of investigating these variables. Aims: The purpose of this study was to assess the relationshipsof problem solving skills and spiritual intelligence with the tendency to Internet addiction according the mediating role of rumination. Method: Using descriptive-correlation study, 353 Internet users (19-35 year old) were selected randomly. The evaluation of the proposed model was done by modeling structural equations.Computer and SPSS and lisrel software were used for statistical calculations and analysis. Results: The research results showed that the research model fits well.The results of Pearson correlation coefficient test showed that there is a negative and significant relationship between the variables of problem solving skills and spiritual intelligence on the rate of Internet addiction (p<0.01). Conclusions: Intrnt addiction hasdiffent behavoural coorelates such as problem solving and sprotual intelligence that can be moderated by various process.